Tocotrienols and its Role in Cardiovascular Health- a Lead for Drug Design - R Vasanthi, Hannah; P. Parameswari, R.; K. Das, Dipak (Current Pharmaceutical Design, 2011)
The worldwide cardiovascular disease (CVD) burden has resulted in an intense interest in pharmaceutical approaches to combat this multifactorial disease. Vitamins are high-flying among natural or endogenous compounds, considered to be beneficial to human health and have become attractive targets for research. Of all the vitamins, tocopherols and tocotrienols, parent congeners in the vitamin E family, are found to be effective in decreasing mortality due to CVD. As understanding of the antioxidant effect of this vitamin evolved, tocotrienols gained eminence in recent years and researchers begun to further study the biological effects of it. Tocotrienols have several cardioprotective effects; including antagonizing the oxidation of low density lipoproteins, anti atherosclerotic, inhibiting platelet aggregation and monocyte adhesion, preventing smooth muscle proliferation and various other cardiovascular disorders. Recent studies have also revealed the molecular targets of the tocotrienols and their roles in cancer, bone resorption, diabetes and neurological diseases at both preclinical and clinical levels. The multitargeted role of tocotrienols in most degenerative diseases proves it to be an ideal candidate as a nutraceutical/pharmaceutical agent for useful exploitation.
Keywords: tocopherols